Studies on Some Anionic Complexes of Cobalt(II), Nickel(II) and Copper(II)— Part(II) - Naik, S.; Purohit, K.M.; Patel, R.N. (Asian Journal of Chemistry, 2010)
A series of complexes of the type [LH2] [MCl4L'2],where L = hexamethylenediamine; M = Co(ll), Ni(lI) or Cu(II).L' = pyridine (Py), γ-picoline (γ-pic), quinoline (Qn), pyridine-Noxide(Py-NO) and γ-picoline-N-oxide (γ-pic-NO) have been preparedand characterized on the basis of elemental analysis,molecular weight measurements, molar conductance room temperaturemagnetic moment, infrared and electronic spectral data.